(untitled) (Borneo Engineering & Advanced Multidisciplinary International Journal, 2024)
The research study aims to develop and characterize a hybrid coconut fiber-polyester composite board with the addition of fiberglass as a reinforcement. The study’s main objective was to investigate the composite board flexural strength and evaluate the fiberglass’s effects on its mechanical properties. The research methodology involved the fabrication of the composite board using a hand-lay-up technique. Coconut fibers were manually extracted from the trunk and processed into small powder-like pieces. Flexural tests were conducted using a Universal Testing Machine by ASTM D790 standards. The results showed the highest performance of flexural strength for the composites with 10% coconut fiber with addition of 10% fiberglass with the value of 509.05 N/mm2. The composites with 10% coconut fibers with no addition of fiberglass exhibited the lowest flexural strength with the value of 173.61 N/mm2. This indicates that fiberglass plays a crucial role in enhancing the bending strength of the composite material. The study concludes that the hybrid coconut fiber-polyester composite board with the addition of fiberglass exhibits promising mechanical properties, particularly in terms of flexural strength. The study recommends further exploration of fiber treatment methods to improve the adhesion between the coconut fibers and the polyester matrix. Additionally, the evaluation of the composite's environmental impact and the investigation of advanced fabrication techniques, such as resin infusion or compression molding, are suggested to optimize the production process and enhance the quality of the composite. Overall, the study contributes to the understanding of the mechanical properties of the hybrid coconut fiber-polyester composite board and its potential applications in various industries.